ASPEK HUKUM KEWIRAUSAHAAN - Astri Mulyanita (Sekolah Tinggi Ilmu Hukum Awang Long, 2021)
Entrepreneurship is the process of creating something else creatively and innovatively by taking advantage of available opportunities. Or in other words, entrepreneurship is the creative and innovative ability of a person who is used as a basis and resource to seek opportunities for success. The importance of the legal aspect for a business is very necessary, because with the status of a legal entity is an important basis when we start entrepreneurship, the company must have a certain legal entity in order to have legality in carrying out its activities. The existence of a company legal entity will protect the company from all claims due to the activities it carries out. Because corporate legal entities provide certainty for doing business, so that concerns over legal violations can be anticipated, or avoided, given that the company's legal entities have signs that must be obeyed. By having a legal entity, the company will fulfill the obligations and rights of various parties related to the company, both inside and outside the company.